African women entrepreneurs and COVID-19: Towards achieving the African Union Agenda 2063 - Anwana, Emem O. (HTS teologiese studies, 2022)
Research on the challenges facing African women entrepreneurship and the impact of the coronavirus disease 2019 (COVID-19) pandemic is scant. This article explored the challenges and the impact of COVID-19 on African women-owned businesses and the effect thereof on the 17th goal of the African Union (AU) Agenda 2063. African women entrepreneurs experience many social inequalities, ranging from cultural norms to family to legal and regulatory measures to accessing finance. The COVID-19 pandemic exacerbated these challenges as many African women entrepreneurs have been forced out of business because of measures taken by African governments to halt the spread of the disease. The article reviewed current literature on African women entrepreneurs and the impact of the COVID-19 pandemic using two databases and is based on a total of 104 published articles. The article provided a foundation for post-COVID-19 policy directives in Africa. The authors recommend measures to mitigate these challenges and discuss strategies for policymakers to re-position African women entrepreneurs for the post-COVID-19 era towards achieving AU Agenda 2063 and realising the Africa we all want.Contribution: The study aligns with the United Nations Sustainable Development Goal of ending poverty in Africa and the AU Agenda 2063 goal of achieving gender equality and empowerment of all women and girls to achieve the Africa we all want.